Materials, design and manufacturing for lightweight vehicles - Mallick, P. K., 1946- (Boca Raton, Fla. : CRC Press ; Oxford : Woodhead, 2010)
"Research into the manufacture of lightweight automobiles is driven by the need to reduce fuel consumption to preserve dwindling hydrocarbon resources without compromising other attributes such as safety, performance, recyclability and cost. This book helps engineers to not only learn about the materials being considered for lightweight automobiles, but also to compare their characteristics and properties. It discusses materials for lightweight automotive structures and reviews manufacturing and design of lightweight automotive structures. With its distinguished editor and renowned team of contributors, this book will aid the design and material selection for motor vehicle bodies and components."--Publisher's description.
Overview -- Advanced steels for lightweight automotive structures -- Aluminum alloys for lightweight automotive structures -- Magnesium alloys for lightweight powertrains and automotive structures -- Thermoplastics and thermoplastic-matrix composites for lightweight automotive structures -- Thermoset-matrix composites for lightweight automotive structures -- Manufacturing processes for light alloys -- Joining for lightweight vehicles -- Recycling and life cycle issues for lightweight vehicles -- Crashworthiness design issues for lightweight vehicles.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Motor vehicles -- Design and construction; Motor vehicles -- Materials; Lightweight construction; TECHNOLOGY & ENGINEERING / Engineering (General); Electronic books